Efektivitas Instalasi Pengolahan Air Limbah pada Effluent Treatment Unit (ETU) PT Lotte Chemical Titan Nusantara - Frebhika Sri Puji Pangesti; Anis Masyruroh; M. Hikmatiar (Fakultas Teknik, 2018)
PT Lotte Chemical Titan Nusantara (PT LCTN) is a Korean Foreign Investment Company in Cilegon City which is a polythylene producing industry. PT LCTN produces waste water into the sea. Wastewater treatment refers to the Decree of the Minister of Environment Number 22 of 2011 on the Permit for Disposal of Wastewater into the Sea of PT Titan Petrokimia Nusantara. Thepurpose of the research is to identify the problem and the improvement step in wastewater treatment. The effectiveness of wastewater treatment erformance at ETU (Effluent Treatment Unit) in 2015, especially on test parameters such as Total Dissolved Solid, TSS (Total Suspended Solid), Nitrate, Nitrite, BOD (Biochemical Oxygen Demand) and COD (Chemical Oxygen Demand). Statistical analysis SPSS Version 22 shows the average value of inlet and outlet there is a difference because the value of trithmetic is smaller than t table. In other words can give a significant influence on theinlet and outlet. Percentage effectiveness of TDS reach 33,33%, TSS reach 91,67%, nitrate reach 25% while for nitrite reach 83,33%.